1997
DOI: 10.2135/cropsci1997.0011183x003700020021x
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Spot Blotch Resistance in Four Spring Wheat Populations

Abstract: Spot blotch of wheat (Triticum aestivum L.), caused by Bipolaris sorokiniana (Sacc.) Shoem, is serious constraint in South Asia, and leading cultivars have low levels of resistance. The response to selection for low and high area under disease progress curve (AUDPC) of spot blotch in four wheat populations, involving different Chinese hexaploid parents with high level of resistance and a commercial cultivar moderately resistant to spot blotch, was investigated. Selections were made in the F3 generation for low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…There was a significant negative correlation between AUDPC and heading or maturity confirming the difficulty experienced by wheat scientists in South Asia attempting to improve these two important traits simultaneously (Sharma et al, 1997a;Dubin et al, 1998). However, the magnitude of correlation between AUDPC and heading especially for long duration genotypes (r = 0.421) underlines the possibility of identifying early maturing resistant genotypes in segregating generations as suggested by Sharma & Figure 1.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…There was a significant negative correlation between AUDPC and heading or maturity confirming the difficulty experienced by wheat scientists in South Asia attempting to improve these two important traits simultaneously (Sharma et al, 1997a;Dubin et al, 1998). However, the magnitude of correlation between AUDPC and heading especially for long duration genotypes (r = 0.421) underlines the possibility of identifying early maturing resistant genotypes in segregating generations as suggested by Sharma & Figure 1.…”
Section: Resultsmentioning
confidence: 80%
“…Disease assessment was started when necrotic symptoms appeared on the penultimate leaves. Disease severity was recorded by visually scoring the percent diseased area of the flag (F) and penultimate (F-1) leaves (da Luz & Bergstrom, 1986;Sharma et al, 1997a). Four disease readings were recorded between 85 and 106 days after sowing, at intervals of 5 to 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…Disease assessment Ten primary tillers within each plot were randomly tagged to score spot blotch severities, which were recorded by visually scoring the percentage diseased area of the flag (F) and penultimate (F-1) leaves (Sharma et al 1997). Three disease readings were recorded between growth stages DC 69 and 83 (Zadoks et al 1974), at 5-7-day intervals.…”
Section: Field Experimentsmentioning
confidence: 99%
“…However, Sharma and Bhatta (1999) and Joshi et al (2002) reported that the days to heading and spot blotch resistance segregated independently in crosses involving early-maturing susceptible and late-maturing resistant genotypes. Sharma et al (1997a) showed that kernel weight and spot blotch resistance were not correlated in some of the crosses involving a well-adapted susceptible cultivar with high grain weight and a less well-adapted resistant genotype with low grain weight. Adapted susceptible wheat cultivars in South Asia show high kernel weight primarily because of early maturity, while the less well-adapted resistant genotypes have a low kernel weight because of their late maturity, a negative characteristic in warm wheat-growing environments because the longer grain filling period is curtailed by high temperatures (Dubin et al, 1998;Sharma et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…Considering independent segregation of maturity and spot blotch resistance (Sharma & Bhatta, 1999;Joshi et al, 2002) and the absence of a negative correlation between grain weight and resistance (Sharma et al, 1997a), Sharma and Duveiller (2003) successfully used a selection index to simultaneously improve resistance, maturity and grain weight in the F 4 generation. These three traits determine the commercial acceptance of a wheat cultivar in the region.…”
Section: Introductionmentioning
confidence: 99%